Case-Control Study of Individuals with Discrepant Nucleocapsid and Spike Protein SARS-CoV-2 IgG Results. (17th May 2021) - Wang, Hannah; Wiredja, Danica; Yang, Lu; Bulterys, Philip L; Costales, Cristina; Röltgen, Katharina; Manalac, Justin; Yee, Jennifer; Zehnder, James; Shi, Run Zhang; Boyd, Scott D; Pinsky, Benjamin A
Abstract: Background: Laboratory-based methods for SARS-CoV-2 antibody detection vary widely in performance. However, there are limited prospectively-collected data on assay performance, and minimal clinical information to guide interpretation of discrepant results. Methods: Over a 2-week period, 1080 consecutive plasma samples submitted for clinical SARS-CoV-2 IgG testing were tested in parallel for anti-nucleocapsid IgG (anti-N, Abbott) and anti-spike IgG (anti-S1, EUROIMMUN). Chart review was conducted for samples testing positive or borderline on either assay, and for an age/sex-matched cohort of samples negative by both assays. CDC surveillance case definitions were used to determine clinical sensitivity/specificity and conduct receiver operating characteristics curve analysis. Results: There were 52 samples positive by both methods, 2 positive for anti-N only, 34 positive for anti-S1 only, and 27 borderline for anti-S1. Of the 34 individuals positive for anti-S1 alone, 8 (24%) had confirmed COVID-19. No anti-S1 borderline cases were positive for anti-N or had confirmed/probable COVID-19. The anti-N assay was less sensitive (84.2% [95% CI 72.1-92.5%] vs 94.7% [95% CI 85.4-98.9%]) but more specific (99.2% [95% CI 95.5-100%] vs 86.9% [95% CI 79.6-92.3%]) than anti-S1. Abbott anti-N sensitivity could be improved to 96.5% with minimal effect on specificity if the index threshold was lowered from 1.4 to 0.6. Conclusion: Real-world concordance between different serologic assays may be lower than previously described in retrospective studies. These findings have implications for the interpretation of SARS-CoV-2 IgG results, especially with the advent of spike antigen-targeted vaccination, as a subset of patients with true infection are anti-N negative and anti-S1 positive.